Etiology of viral meningitis in Aleppo-Syria: a retrospective study - Yahia, Mohammad Ammar Mohamad Kais; Bery, Kaumudi; Alherk, Muhamad; Kaddor, Samer Haj (International Journal of Research in Medical Sciences, 2022)
Background: Viruses are the most common causative agents of aseptic meningitis syndrome. This study aimed to identify the most common causes of viral meningitis (VM) by polymerase chain reaction (PCR) and study its relationship with age and seasonal variations. Methods: During the study period, the records of 129 patients who had been discharged and diagnosed with VM were identified and reviewed. Cerebrospinal fluid (CSF) samples collected from these patients were tested by PCR using the Seeplex V1 AC meningitis detection kit that detects herpes simplex virus type 1 and type 2 (HSV1) and (HSV2), varicella-zoster virus (VZV), cytomegalovirus (CMV), Epstein-Barr virus (EBV), human herpesvirus type 6 (HHV6), and the Seeplex V2 AC meningitis detection kit that detects human enteroviruses (EV). Results: VM was confirmed by PCR in 79 cases (61.42%). Most of the VM cases were reported in children younger than 6 years (72.15%; 57/79). EV were detected at the highest incidence of 60 cases (75.9%), followed by HSV1and EBV in 6 cases for each (7.6%, each), CMV in 3 cases (3.9%), VZV and HHV6 were detected in 2 cases for each (2.5%, each). VM cases were found to be more frequent during the spring season (64.6%; 51/79) and the peak incidence of enteroviral meningitis cases was during the spring season (68.4%; 41/60). Conclusions: Our study showed that EV were the most common causative agent of VM in Aleppo-Syria. Genotype and serotype of identified viruses are recommended.